Biossíntese de nanopartículas de ouro por Paenibacillus polymyxa e Paenibacillus terrae - Carvalho, Carina Miranda (Universidade Federal de São Carlos, 2020)
In order to synthetize gold nanoparticles utilizing a green process, this work intended to produce nanoparticles using bacterial crude extract. Paenibacillus polymyxa (PP) and P. terrae (PT) have biotechnological interest in medical field, and some studies have been showing the potential of endophytic microorganisms in the production of antitumoral and antibacterial substances. Nanoparticles biosynthetic techniques are no toxic and clean when compared to traditional ones, where there is intensive energy consumption and sometimes may involve toxic chemical substances. Metallic nanoparticles have important applications in medical field, specially the gold ones. Through the nanoparticles biosynthesis using P. polymyxa and P. terrae, the process was optimized considering the synthesis time, the extract concentration, the wavelength and the particle size. The experiment was divided into phases where the best focus (1, 1: 2, 1: 4, 1: 8 and 1:16) was analyzed, observing through UV-Vis spectroscopy (without visible ultraviolate) at 540 nm the best absorption of light (how much) in relation to time and over 72 hours in a 12-hour interval. As the best indicators were 1: 2 and 1: 4, for both phyto-bacterial extracts and 12 to 24 hours as the best periods. The next phase was analyzed hourly for 24 hours, with the values 1: 2 and 1: 4, for (in relation to) light absorption at 540 nm and in the spectral range of 300 to 800 nm, demonstrating a statistic of gold nanoparticle for 1: 2 dilution, whose peak at around 540 nm, and as of 7 am are already described. Based on the results of the characterization by DLS (Dynamic Light Scattering - Dynamic Light Scattering) and absorbance, such as gold nanoparticles synthesized through crude extractions PP 1: 2 and PT 1: 2 were as obtaining better results, obtaining the average level of 262 nm and 372 nm, respectively, in monodispersed systems, with the following analyzes (occurrences) after 7 hours of biosynthesis reaction, obtaining greater results between 12 and 24 hours. The main absorption was detected at the red spectral range.
Biosynthesis of gold nanoparticles by Paenibacillus polymyxa and Paenibacillus terrae
Keywords: Fitobactéria; Nanopartículas metálicas; Síntese verde; Cerrado; Phyto-bacteria; Metallic nanoparticles; Green synthesis; CIENCIAS BIOLOGICAS::MICROBIOLOGIA